ANALISIS PENGARUH FAKTOR SOSIAL DEMOGRAFI TERHADAP INTENSITAS PENGGUNAAN JAMINAN KESEHATAN BALI MANDARA DI KABUPATEN BULELENG - Intan Yuli Bhestari; I Ketut Sudibia; AAIN Marhaeni (PIRAMIDA, 2016)
The low quality of public health, especially the poor caused by several factors, namely the lack of awarenessto maintain physical health, environmental hygiene and unhealthy lifestyle, and financing to gain access to goodhealth. This study aims to analyze; 1) the recipient perceptions JKBM to services JKBM, 2) analyze the influence ofthe distance of residence, education, household size and tenure of the income users JKBM, 3) analyze the influenceof the distance of residence, education, family size, employment, and income to the intensity of use JKBM and 4)analyzing the income of the recipient JKBM role in mediating the effect of variable area of residence, education,household size and tenure of the intensity of use JKBM in Buleleng. Data collection methods used were interviewsand questionnaires, with a number of respondents as many as 119 people. The analytical tool used is descriptiveanalysis and path analysis. The results of the analysis of the recipient’s perception JKBM JKBM to health servicesin low category, the perception is very satisfied with the intensity of use JKBM. Distance shelter, and education,and a significant positive effect on revenues. Education and income of a significant negative effect on the intensityof use JKBM. Revenue fully mediate between the distance of a place to stay on the intensity of use JKBM.